Evaluasi dan Analisis Prospektif Manajemen Risiko pada Bank Jatim - Amilatus Nafisah; Endah Mudiyatul Kustinah; Francisca Galuh Dewanti; Renny Oktafia (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
. This study applies a prospective analysis approach in evaluating the financial performance of Bank Jatim, by considering both internal and external factors. Prospective analysis is used to predict the bank's future financial performance based on current conditions and projections of various factors that affect it. This study evaluates the projected growth of assets such as loans, investments, and other productive assets; additional capital/equity from retained earnings and rights issues; projected operating profit and net profit for the next few years; and analysis of credit risk management, market risk, liquidity risk, and operational risk. External factors such as macroeconomic conditions, government regulations, foreign exchange rates, industry competition, and socio-political factors are also considered in this prospective analysis. This research is expected to provide recommendations for Bank Jatim on how to maintain and improve its financial performance in the future by considering various internal and external factors.